A tale of three common nipple diseases. Issue 3 (4th May 2022) - Alkul, Mahmud; Lin, Christine P.; Truitt, Jay; Tarbox, Michelle B.
Abstract: Paget's disease of the nipple is a rare breast carcinoma of the nipple-areola complex and is often associated with an underlying in situ or invasive carcinoma. It clinically presents as a thickened, erythematous, weeping or crusted lesion with irregular borders. Paget's cells invading the epidermis are the hallmark histopathologic feature, and cytokeratin 7 staining is positive in nearly all cases. However, the diagnosis of Paget's disease may be delayed or missed in favor of clinically similar benign nipple processes such as nipple adenoma and nipple dermatitis. We present a case of Paget's disease of the nipple in a 73-year-old woman with a brief review of other common nipple diseases.